Standardized Nutritional Care Process Management Of Pediatric Patients With Congenital Heart Disease And Malnutrition - Kuddah, Najla; Sholehah, Lisa Farhatus (JURNAL KESMAS DAN GIZI (JKG), 2025)
Congenital heart disease can be experienced early in life. This disorder can cause growth disorders in children, one of which is malnutrition. Malnutrition can be caused by food intake that does not meet the needs and can be influenced by chronic diseases. This study aims to determine the results of the implementation of a standardized nutritional care process in pediatric patients with OBS dyspnea, VSD, Pneumonia, FTT, Malnutrition. This case study was conducted for 3 days on October 01, 2024 - October 03, 2024 located at z hospital in Surabaya. this research method uses an analytic observational design on outpatients.  The nutritional care process begins with an assessment based on medical record data and interviews consisting of food intake, anthropometer, biochemical, and physical/clinical data. Followed by diagnosis, intervention, monitoring and evaluation. The results of this study showed an increase in the patient's food intake but still did not meet the patient's needs, the patient's physical/clinical examination improved but the patient's airway was still ineffective. The conclusion of the study is that the management of the patient's nutritional care process can optimize the patient's condition but still does not reach the target needs.